Vicar forane's visit in canonic-pastoral terms - ADAMCZYK, JERZY (Prawo Kanoniczne, 2018)
The following article is devoted to vicar forane's visit in canonic-pastoral terms. At first, the vicar forane’s visit is presented in the historic view. Then, the issue, nature and necessity of vicar forane’s visit is discussed. The final part of the article is connected with the subject of vicar forane’s visit in the parishes of vicariate forane.